The algorithmic model of information technology for forming strategic portfolio of enterprise goods - Чернышева, Дарья Александровна; Лисицкий, Василий Лаврентьевич (Technology audit and production reserves, 2014)
Enterprise with the incremental style of behavior, conducting business activity in conditions of dynamic competitive environment, characterized by instability of its main factors and their uncertainty in time is considered. The problem of an adequate algorithmic model for forming a strategic portfolio of enterprise goods, which satisfies the system requirements to achieving the set strategic goals by the enterprise is solved. Algorithmic model integrates qualitative and quantitative methods for modeling enterprise business activity; contains algorithmic models of expert procedures for determining the morphology of the strategic portfolio of goods, ranking strategic goods by risks, as well as an algorithmic model for determining the optimal structure of the strategic portfolio of enterprise goods. The proposed algorithmic model is the theoretical basis of information technology that automates forming an effective strategic portfolio of goods, information and analytical decision support in the strategic management of the functioning and development of modern enterprises. The features of creating information technology based on the proposed model are considered.